Clumber, Nottinghamshire: The Rise and Fall of a Ducal Library. (2nd April 2016) - Purcell, Mark
Abstract : Clumber Park, the family seat of the Dukes of Newcastle, was demolished in 1938, and its contents, including several thousand books, were dispersed at auction. Although it may now be deemed a 'lost' library, sale catalogues give a clue to the treasures that were dispersed, while the history of the family explains how yet another aristocratic library came to be sold off. This case study comprises a contribution towards the necessity of recording dispersed libraries.